2022
DOI: 10.55576/job.v2i4.23
|View full text |Cite
|
Sign up to set email alerts
|

Cost of OR Time is $46.04 per Minute

Abstract: Objectives: The purpose of this study is to establish a consensus estimate of operating room cost per minute based on currently published literature. Design: Literature review. Main outcome measurement: Operating room cost per unit time. Results and conclusions: Google Scholar search produced 51 articles regarding ““operating room cost per minute” of which 14 had novel estimates for OR cost per minute. The mean of these estimates was $46.04 ± $32.31. There was little consistency in methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Increased operative time may be due to general factors such as positioning, induction, and intubation, or technical challenges during surgery, such as more tissue to dissect and suture. This has significant financial implications, as average operating costs have increased from $20/min in 1991 to $46/min in 2022 30–32 . While operative times may increase with a higher BMI given that there may be more tissue to dissect and reconstruct, physician experience in oncoplastic surgery also plays an independent role in OR time efficiency, with an increased experience level leading to less operative time 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased operative time may be due to general factors such as positioning, induction, and intubation, or technical challenges during surgery, such as more tissue to dissect and suture. This has significant financial implications, as average operating costs have increased from $20/min in 1991 to $46/min in 2022 30–32 . While operative times may increase with a higher BMI given that there may be more tissue to dissect and reconstruct, physician experience in oncoplastic surgery also plays an independent role in OR time efficiency, with an increased experience level leading to less operative time 14 .…”
Section: Discussionmentioning
confidence: 99%
“…An article by reported additional time of 21-30 min for manually searching the needle and additional 31-40 min for x-ray totaling 70 min of added OR time. The OR cost per minute has been previously reported to be $16-$115 (Smith et al, 2022). However, when considering studies after 2020, the cost is $62-$115 (Smith et al, 2022).…”
Section: Cost Burden Of the Current Retrieval Protocolmentioning
confidence: 99%
“…The OR cost per minute has been previously reported to be $16-$115 (Smith et al, 2022). However, when considering studies after 2020, the cost is $62-$115 (Smith et al, 2022). Thus, the additional time translates into a cost of $4340-$8050.…”
Section: Cost Burden Of the Current Retrieval Protocolmentioning
confidence: 99%
“…Results of a 2022 literature review showed that the mean OR time cost per minute was $46.04 (SD = $32.31). 5 Using an estimate of $46 per minute, a 15-minute delay at the beginning of the day in one OR for 250 weekdays would cost a facility $172,500 annually. Although perioperative leaders and nurses may associate procedure delays with weekday surgery schedules, in some instances, facility leaders may plan scheduled procedures on weekends.…”
Section: Significance Of the Problemmentioning
confidence: 99%
“…Delays at the beginning of the day may adversely affect patients, surgeons, anesthesia professionals, perioperative personnel, and inpatient nurses. Results of a 2022 literature review showed that the mean OR time cost per minute was $46.04 (SD = $32.31) 5 . Using an estimate of $46 per minute, a 15‐minute delay at the beginning of the day in one OR for 250 weekdays would cost a facility $172,500 annually.…”
Section: Significance Of the Problemmentioning
confidence: 99%